2020
DOI: 10.1021/acs.jpcc.0c00891
|View full text |Cite
|
Sign up to set email alerts
|

Shear-Induced Carbon Nanotube Migration and Morphological Development in Polylactide/Poly(vinylidene fluoride) Blend Nanocomposites and Their Impact on Dielectric Constants and Rheological Properties

Abstract: Polymer composites featuring high dielectric constants are known to be useful materials for the development of modern transducers, piezo- and thermal-sensors, and energy storage devices. In this study, blend nanocomposites of carbon nanotube (CNT)-containing (0.25, 0.75, and 1.0 wt %) polylactide (PLA)/poly­(vinylidene fluoride) (PVDF) (70/30 w/w) are developed by melt-mixing PVDF-CNT composite with PLA in a twin-screw extruder. The novelty of this process lies in the fact that the CNTs can migrate from the PV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…Moreover, similar behavior has been reported in a CNT‐based composite, where an increase in G ′ and improved electrical properties were attributed to the deagglomeration of spherical CNT bundles over time. [ 85,86 ] Thus, the same reasoning can be applied here to explain the modulus evolution during annealing (Figure 6A). SEM images (Figure 7) support this reasoning.…”
Section: Resultsmentioning
confidence: 87%
“…Moreover, similar behavior has been reported in a CNT‐based composite, where an increase in G ′ and improved electrical properties were attributed to the deagglomeration of spherical CNT bundles over time. [ 85,86 ] Thus, the same reasoning can be applied here to explain the modulus evolution during annealing (Figure 6A). SEM images (Figure 7) support this reasoning.…”
Section: Resultsmentioning
confidence: 87%
“…[ 8–13 ] Development of PLA composites with organic or inorganic nanoparticles could be an alternative, low cost, and versatile approach to improve the PLA's crystallization and rheological properties and hence its processability. [ 13–22 ] Cellulose nanocrystals (CNC) are one of the most attractive natural fillers to develop fully green nanocomposites due to their high specific surface area, high aspect ratio, high modulus, biocompatibility, nontoxicity, and low density. [ 23–28 ] While the crystallization and rheological properties of PLA could be improved with the addition of CNC, the service temperature and barrier properties of PLA could also be enhanced significantly upon the CNCs well dispersion in the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the two-step extrusion helped CNTs gather at the interface and form a conductive network. [131] Highly porous composite foams using three carbonbased fillers, thermally rGO-CNTs (TG-CNs), chemically rGO-CNTs (RG-CNs), graphene nanoplate-CNTs (GN-CNs), and their equivalent G-CNT/PMMA nanocomposite foams were synthesized. The TG-CN/PMMA foams performed comparatively better than the other two hybrids, with an electrical conductivity of 2.92 S/m and shielding effectiveness of 30 dB in the X-band at 10 wt% loading.…”
Section: F I G U R E 7 Graphical Representation Of the Fabrication Pr...mentioning
confidence: 99%